2016
DOI: 10.1038/cgt.2016.61
|View full text |Cite
|
Sign up to set email alerts
|

Imaging techniques: new avenues in cancer gene and cell therapy

Abstract: Cancer is one of the world's most concerning health problems and poses many challenges in the range of approaches associated with the treatment of cancer. Current understanding of this disease brings to the fore a number of novel therapies that can be useful in the treatment of cancer. Among them, gene and cell therapies have emerged as novel and effective approaches. One of the most important challenges for cancer gene and cell therapies is correct monitoring of the modified genes and cells. In fact, visual t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 64 publications
0
39
0
Order By: Relevance
“…The utilization of imaging techniques is one of main approaches for detection and assessment response to therapy in patients with breast cancer (Khalkhali, Mena, & Diggles, ). Multiple lines of evidence indicated that various imaging techniques such as mammography, MRI, PET, CT, and SPECT could be employed as effective tools for assessment patients with various cancer such as breast cancer, giloma, oral cancer, and melanoma (Keshavarzi, Darijani, et al, ; Keshavarzi, Sorayayi, et al, ; Khanmohammadi, Mir, Baniebrahimi, & Mirzaei, ; Saadatpour et al, ; Saadatpour, Bjorklund, et al, ). Growing evidences revealed that imaging techniques are associated with some limitations such as expensive (Andreea et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of imaging techniques is one of main approaches for detection and assessment response to therapy in patients with breast cancer (Khalkhali, Mena, & Diggles, ). Multiple lines of evidence indicated that various imaging techniques such as mammography, MRI, PET, CT, and SPECT could be employed as effective tools for assessment patients with various cancer such as breast cancer, giloma, oral cancer, and melanoma (Keshavarzi, Darijani, et al, ; Keshavarzi, Sorayayi, et al, ; Khanmohammadi, Mir, Baniebrahimi, & Mirzaei, ; Saadatpour et al, ; Saadatpour, Bjorklund, et al, ). Growing evidences revealed that imaging techniques are associated with some limitations such as expensive (Andreea et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is one of the important diseases that are associated with various public health problems in the world . Hence, fast and suitable diagnosis platforms are needed . Several studies reported that a variety of approaches such as cell therapy, immunotherapy, gene therapy, and nanotechnology‐based methods could be applied in the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on the identification and finding new therapies for cancer treatment (Mirzaei, Naseri, et al, ; Mirzaei, Yazdi, et al, ; Saadatpour, Bjorklund, et al, ). It has been shown that present therapies could not provide satisfactory effects for patients with cancer (Mirzaei, Sahebkar, Jaafari, et al, ; Saadatpour, Fadaee, et al, ; Saadatpour, Rezaei, et al, ; Salarinia et al, ). Hence, new therapies to overcome the limitations of conventional therapies are necessary (Mirzaei, Sahebkar, et al, ).…”
Section: Introductionmentioning
confidence: 99%